2021
DOI: 10.5455/msm.2021.33.45-50
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Healthcare Professionals in Issues that Relate to Quality Management

Abstract: Background: The health sector should adopt integrated quality systems because of the need to survive and develop in a highly competitive environment. Inefficiency of mechanistic procedures, along with inadequate administrative infrastructure, impose innovative appoaches to improve operations and increase revenues by reducing quality feilures. Objective: A health system that relies on quality healthcare services can directly benefit the entire society, may reduce mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Besides, different healthcare providers and healthcare institutions get the feeling that quality is imposed on them and are less motivated to create their own bottom‐up quality system 8,9 . This might be detrimental to patient safety, as a recent review has demonstrated that healthcare professionals' contribution to quality can lead to improved patient safety 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, different healthcare providers and healthcare institutions get the feeling that quality is imposed on them and are less motivated to create their own bottom‐up quality system 8,9 . This might be detrimental to patient safety, as a recent review has demonstrated that healthcare professionals' contribution to quality can lead to improved patient safety 10 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 This might be detrimental to patient safety, as a recent review has demonstrated that healthcare professionals' contribution to quality can lead to improved patient safety. 10 In Flanders, Belgium, a coalition government agreement was established in 2009 as the basis for quality in acute-care hospitals. 11 This agreement introduced a 'Quality-of-Care Triad' consisting of three main components: voluntary hospital-wide accreditation by an international external agency, voluntary measurement and public BROUWERS Et al.…”
Section: Introductionmentioning
confidence: 99%
“…AI creates more opportunities for frontline healthcare staff to efficiently engage in direct patient care. [ 31 ] This optimization of workflows and resource allocation encompasses aspects,[ 32 ] including predicting patient volumes,[ 33 ] aiding appointment management,[ 34 ] facilitating communication, addressing supply chain demands,[ 35 ] ensuring equitable workload distribution,[ 36 ] optimizing staff schedules,[ 36 ] and automating processes. [ 37 ] These improvements also extend to appointment scheduling,[ 34 ] electronic check-ins at medical facilities,[ 38 ] automated reminders for follow-up appointments,[ 39 ] and immunization schedules for children,[ 40 ] as well as the usage of AI-driven algorithms for determining drug dosages and issuing warnings regarding potential adverse effects when prescribing combinations of multiple medications.…”
Section: Applications Of Ai In Hospital Based-improvement Levelmentioning
confidence: 99%
“…Treating the team members with dignity and improving their self-worth is necessary to control their negative behaviors. Healthcare leaders must provide clear instructions to contenders regarding their improvement areas while maintaining the confidentiality of their performance reviews [76]. This measure is essential to strengthen their sense of professional growth while safeguarding their identity.…”
Section: Leadership Tactics For Conflict Management/preventionmentioning
confidence: 99%
“…The prompt anticipation of employee responses, while addressing professional conflicts, is paramount to deciding the next steps for their effective resolution [75]. The establishment of open feedback channels is the final step to improve transparency and develop potential measures for diffusing workplace conflicts [76].…”
Section: Leadership Tactics For Conflict Management/preventionmentioning
confidence: 99%